Memórias de uma experiência intercultural em torno do artesanato de Porto Nacional, Tocantins entre 1975 e 1981 - Lotufo, Edith Hedwig (2015)
This work aims to recover and discuss an experience lived between 1975 and 1981 in a recovery project of regional craft in Porto Nacional, north Goiás. This work as one of the community activities of the Community of Health, Development and Education - Comsaúde led to the creation of the Association of Artisans and Craftsmen of Porto Nacional - Associara. The inquiry, based on archives and memories searches several access routes to check the meanings of the experience to the life of artisans. The prospect of Visual Culture that based methodological paths of studies highlighted the various thematic interrelationships involved in past work as: Education and Popular Culture based on Paulo Freire, the relationship between craft and design and public policies for the area. This research allowed to hear different voices and pointed new visions of human centered design and ways of living, producing and solve problems in a complex world. This route brought aspects of the past to current discussions intertwining crafts, design, culture, living together and sustainability. The archival inquiry and the analysis of the interviews with three artisans showed that the craft enhancement project contributed to craft activities practiced in the field could become professional activities recognized in the city of Porto Nacional. People with migration histories found in traditional crafts and collective forms of work opportunities to value their culture and exercise their citizenship.